2003
DOI: 10.1073/pnas.1130102100
|View full text |Cite
|
Sign up to set email alerts
|

Guanylate cyclase-activating protein (GCAP) 1 rescues cone recovery kinetics in GCAP1/GCAP2 knockout mice

Abstract: Mediated by guanylate cyclase-activating proteins (GCAPs), cytoplasmic Ca 2؉ levels regulate the activity of photoreceptor guanylate cyclase (GC) and the synthesis of cGMP, the internal transmitter of phototransduction. When GCAP1 is expressed in transgenic mice on a GCAP null background, it restores the wild-type flash responses in rod photoreceptors. In this communication, we explored the role of GCAP1 in cone photoreceptors by using electroretinograms (ERGs). Under cone isolation conditions, ERGs recorded f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 37 publications
2
48
0
Order By: Relevance
“…ERG recordings on GCAPs −/− mice indicated that deletion of GCAPs delayed the recovery of cone light responses, which were partially restored in mice expressing transgenic GCAP1 on a GCAP null background. 16,17 In a more recent study, single-cell recordings from cones of GCAPs −/− mice gave a detailed picture of the physiological function of GCAPs in cone photoreceptors. 47 Characteristic features of light responses were a 2-fold longer time-to-peak and a 3-fold longer integration time, indicating that GCAPs are required for an efficient shutoff of the response on a short time scale, which is typical for cone response kinetics.…”
Section: ■ What About Cones?mentioning
confidence: 99%
“…ERG recordings on GCAPs −/− mice indicated that deletion of GCAPs delayed the recovery of cone light responses, which were partially restored in mice expressing transgenic GCAP1 on a GCAP null background. 16,17 In a more recent study, single-cell recordings from cones of GCAPs −/− mice gave a detailed picture of the physiological function of GCAPs in cone photoreceptors. 47 Characteristic features of light responses were a 2-fold longer time-to-peak and a 3-fold longer integration time, indicating that GCAPs are required for an efficient shutoff of the response on a short time scale, which is typical for cone response kinetics.…”
Section: ■ What About Cones?mentioning
confidence: 99%
“…GCAPs are the only known activators of retinal guanylyl cyclases (GCs) and are known to be physiological regulators of light adaptation (Mendez et al 2001;Burns et al 2002;Howes et al 2002;Pennesi et al 2003). They are unusual in that they activate GCs when in their Ca 2þ -free form but become inhibitors of GCs at higher Ca 2þ concentrations (Dizhoor and Hurley 1996).…”
Section: Calcium Sensor Proteins In Neuronal Functionmentioning
confidence: 99%
“…Recovery from Test Flashes as Determined by Paired Flash Analysis-A paired flash protocol was used to evaluate the ability of GC deletion mutant retinas to recover responsiveness after light stimulation (23,30,35). In this method, short test flashes followed by varying interstimulus intervals, and a probe flash were used to test for a-wave recovery (36,37).…”
Section: Generation Of Gc2mentioning
confidence: 99%